A practical approach to enlargement of nerves, plexuses and roots. Issue 2 (8th January 2015) - Khadilkar, Satish V; Yadav, Rakhil S; Soni, Girish
Abstract : Detecting enlargement of accessible nerves is very helpful in assessing patients with peripheral nerve disorders, as only a few types of neuropathy lead to nerve thickening. The three leading causes are leprosy, hereditary motor and sensory neuropathies (types 1 and 3) and chronic inflammatory demyelinating neuropathies. MRI, neurography and ultrasonography allow assessment of clinically inaccessible portions of deep-seated nerves, plexuses and roots. As a result, isolated proximal segment thickenings, as found in chronic inflammatory sensory polyradiculopathy, can now be better evaluated and managed. Similarly, focal nerve enlargements due to infection, inflammation, infiltration and neoplasm are being identified and treated effectively. We present a practical approach to the diagnosis and management of patients with enlarged peripheral nerves, plexuses and roots, including cranial nerves.